2021
DOI: 10.1002/1873-3468.14033
|View full text |Cite
|
Sign up to set email alerts
|

AP‐1 and NF‐κB synergize to transcriptionally activate latent HIV upon T‐cell receptor activation

Abstract: Latent HIV‐1 proviruses are capable of reactivating productive lytic infection, but the precise molecular mechanisms underlying emergence from latency are poorly understood. In this study, we determined the contribution of the transcription factors NF‐κB, NFAT, and AP‐1 in the reactivation of latent HIV following T‐cell receptor (TCR) activation using Jurkat T‐cell clones harboring single latent HIV proviruses. Our findings demonstrate that during reactivation from latency, NF‐κB enhances HIV transcription whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…The HIV-1 provirus utilizes the host transcription machinery. Host transcription factors such as NF-κB, specificity protein 1 (Sp1) and activator protein 1 (AP-1) are known activators of HIV transcription [50,51,54]. General transcription factors, mediator, and RNA polymerase II (RNA Pol II) assemble into the preinitiation complex at the 5 -LTR promoter.…”
Section: Transcription Splicing and Protein Expressionmentioning
confidence: 99%
“…The HIV-1 provirus utilizes the host transcription machinery. Host transcription factors such as NF-κB, specificity protein 1 (Sp1) and activator protein 1 (AP-1) are known activators of HIV transcription [50,51,54]. General transcription factors, mediator, and RNA polymerase II (RNA Pol II) assemble into the preinitiation complex at the 5 -LTR promoter.…”
Section: Transcription Splicing and Protein Expressionmentioning
confidence: 99%
“…They observed that, in the crystal structure, the role of Tat is three-fold-namely, scaffolding and stabilization of the Tat-TAR recognition motif (TRM), making specific interactions through its zinc-coordinating loop and making electrostatic interactions through its arginine-rich motif (ARM). Interestingly, most recently, Hokello et al [23] demonstrated that the cellular transcription factor, activator protein-1 (AP-1), synergizes with NF-κB to regulate HIV transcriptional elongation following T-cell receptor activation.…”
Section: Hiv Transcriptional Regulation In the Cnsmentioning
confidence: 99%
“…Recent evidence has shown that unintegrated HIV can also produce viral proteins, which exacerbate the host immune response and lead to excessive toxicity and cell death [9]. Hence, to make ART more effective, research efforts have been diverted to identify the mechanisms through which latent HIV can be reactivated before being targeted by antiretrovirals [9][10][11][12][13]. Latency reversal agents such as romidepsin, JQ-1, and panobinostat have effectively reactivated the peripheral latent viral reservoir.…”
Section: Introductionmentioning
confidence: 99%